Aluminiumgussteile mit zellularem Kern - Körner, Carolin; Hartmann, Johannes (Lightweight Design, 2010)
The relatively expensive production of aluminium foams or structures with a foam core has until now prevented their wide industrial application with high production volumes. This report presents a modified die casting process developed on the basis of polymer foam injection moulding that allows what are known as integral light metal foams to be produced at acceptable costs. These foams feature a compact outer skin with a continuous transition to a cellular core.

Aluminum integral foam castings with microcellular cores by nano-functionalization - Hartmann, Johannes; Blümel, Christina; Ernst, Stefan; Fiegl, Tobias; Wirth, Karl-Ernst; Körner, Carolin (Journal of Materials Science, 2014)
The goal of the present work is the refinement of the pore morphology of aluminum integral foam castings. Integral foam molding, a modified high pressure die casting process, is used where a mixture of melt and blowing agent particles (magnesium hydride, MgH) is injected at high velocity into a permanent steel mold. At the mold surface, decomposition of the blowing agent and pore formation is suppressed due to the high solidification rate whereas solidification of the core is much slower allowing blowing agent decomposition, pore nucleation, and growth. Blowing agent particles not only act as gas suppliers but also represent pore nuclei. Thus, microcellular foam cores can be attained by increasing the number of MgH particles. But increasing the number of powder particles by powder milling strongly decreases the flowability and strong particle agglomeration as a result of the increasing cohesive forces leads to inhomogeneous foams. Flowability of the powder can be restored by coating it with SiO-nano-particles resulting in a homogeneous microcellular foam morphology. © 2013 Springer Science+Business Media New York.

Aluminum integral foams with near-microcellular structure - Hartmann, Johannes; Trepper, André; Körner, Carolin (Advanced Engineering Materials, 2011)
In the present work the influence of the amount and size distribution of blowing agent particles (magnesium hydride, MgH) on the resulting pore structure of aluminum foams is studied. A modified die casting process called integral foam moulding (IFM) is used where aluminum melt mixed with blowing agent is injected into a mould cavity. High cooling rates at the wall of the die result in the formation of a dense shell, whereas, the decomposition of the blowing agent in the inner region leads to a cellular core. Different particle size fractions of MgH are provided by sieving; the resulting pore structures of the foams are analyzed by microcomputed tomography. The results suggest that the pore size distribution represents a direct image of the size distribution of the used powder as well as of the particle density within the melt. This finding allows the production of homogeneous microcellular foams by using a high number of particles with a narrow size distribution. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Aluminum integral foams with tailored density profile by adapted blowing agents - Hartmann, Johannes; Fiegl, Tobias; Körner, Carolin (Applied Physics A: Materials Science and Processing, 2014)
The goal of the present work is the variation of the structure of aluminum integral foams regarding the thickness of the integral solid skin as well as the density profile. A modified die casting process, namely integral foam molding, is used in which an aluminum melt and blowing agent particles (magnesium hydride MgH) are injected in a permanent steel mold. The high solidification rates at the cooled walls of the mold lead to the formation of a solid skin. In the inner region, hydrogen is released by thermal decomposition of MgH particles. Thus, the pore formation takes place parallel to the continuing solidification of the melt. The thickness of the solid skin and the density profile of the core strongly depend on the interplay between solidification velocity and kinetics of hydrogen release. By varying the melt and blowing agent properties, the structure of integral foams can be systematically changed to meet the requirements of the desired field of application of the produced component. © 2014 Springer-Verlag Berlin Heidelberg.

Mikrozellulare Aluminiumintegralschäume - Hartmann, Johannes (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)